2015
DOI: 10.1016/j.jcin.2014.12.249
|View full text |Cite
|
Sign up to set email alerts
|

The 24-Month Prognosis of Patients With Positive or Intermediate Results in the Intracoronary Ergonovine Provocation Test

Abstract: The 24-month prognosis of the positive group in the intracoronary ergonovine provocation test was relatively worse than that of the intermediate group. More intensive clinical attention should be paid to vasospastic angina patients with high-risk factors including frequent angina before angiography, current smoking, and multivessel spasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 26 publications
1
67
0
Order By: Relevance
“…The incidence of VA mortality has been reported by several studies67111213141516171819202122. However, those reports were limited in size and/or duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of VA mortality has been reported by several studies67111213141516171819202122. However, those reports were limited in size and/or duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Japanese nationwide registry data of 1,244 VA patients showed that the incidence of all-cause mortality and cardiac mortality during 2.7 years of follow-up was 1.3% and 0.3%, respectively25. Korean registry data including 2,129 patients with vasospasm revealed that the 2-year incidence of cardiac death was 0.9%19. Considering our study’s considerably longer follow-up duration (median 4.9 years), the rates of cardiac mortality of the previous Korean study could be expected to be similar to ours when the follow-up duration was increased about five fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Furthermore, a recent large registry study showed that patients with a positive ergonovine provocation test had low 24-month incidences of cardiac death, arrhythmia, and acute coronary syndrome (0.9%, 1.6%, and 1.9%, respectively). 36 A risk score (Japanese Coronary Spasm Association Score) has been proposed for prognostic stratification for future major adverse cardiac events and includes the following risk factors: outof-hospital cardiac arrest, tobacco use, angina only at rest, coronary artery disease, multivessel vasospasm, ST-segment elevation on ECG, and β-blocker use. 37 The incidence of major adverse cardiac events in the low-, intermediate-, and high-risk groups was 2.5%, 7.0%, and 13.0%, respectively.…”
Section: February 23 2016mentioning
confidence: 99%
“…Ergonovine maleate is a weak vasoconstrictor, and induces a vasoconstrictor response in susceptible epicardial coronary arteries. This response is mediated by endothelium-independent smooth muscle hyperconstriction and more pronounced with endothelial dysfunction [7,8]. In patients with confirmed variant angina, ergonovine provocation can induce coronary artery spasm at the same site where spontaneous spasm was observed with high diagnostic sensitivity and specificity [9,10].…”
Section: Introductionmentioning
confidence: 99%